Expression of Concepts in Uzbek and Korean Stories (Eurasian Research Bulletin, 2023)
Among the figures of world literature, the artistic prose of Uzbek poetess and writer Saida Zunnunova and Korean writer Pak Wan So are distinguished by their uniqueness. The most important concepts of Uzbek culture are vividly reflected in the work of Saida Zunnunova. From the point of view of the relationship between language and culture, Pak Wan So's art is distinguished by the fact that concepts are expressed as markers of the linguistic and cultural space. Therefore, it is appropriate to compare and reveal the most important concepts in the literary prose of both artists, considering their importance for literary and cultural traditions